2010
DOI: 10.1309/ajcprmd3aruo5wpn
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Expression Level of Epidermal Growth Factor Receptor and Cytokeratin 5/6 Is Significantly Associated With Nodal and Distant Metastases in Patients With Basal-like Triple-Negative Breast Carcinoma

Abstract: Triple-negative (TN) breast carcinoma, characterized by estrogen receptor, progesterone receptor, and HER2 negativity, is a group of aggressive tumors that can be further classified into 2 subtypes: basal-like, defined as CK5/6 and/or epidermal growth factor receptor (EGFR) positive by immunohistochemistry; and non-basal-like. Clinical characteristics and tumor profiles were analyzed in 105 cases of TN tumors. Among these cases, 35 had distant metastasis, 34 had axillary nodal metastasis only, and 36 were noda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…Distant metastases typically occur early in the disease course, with a propensity for visceral metastasis to the lung and brain, rather than the lymph nodes, bone, or liver as seen in non-TNBCs. 30,[32][33][34] The development of targeted therapies is crucial to improve the clinical outcome for these patients. There is a need to further elucidate the molecular basis of TNBC to identify novel prognostic and predictive tumor biomarkers.…”
Section: Distinguishing Between Papillary Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Distant metastases typically occur early in the disease course, with a propensity for visceral metastasis to the lung and brain, rather than the lymph nodes, bone, or liver as seen in non-TNBCs. 30,[32][33][34] The development of targeted therapies is crucial to improve the clinical outcome for these patients. There is a need to further elucidate the molecular basis of TNBC to identify novel prognostic and predictive tumor biomarkers.…”
Section: Distinguishing Between Papillary Lesionsmentioning
confidence: 99%
“…49,50 Although not highly specific and/or sensitive, CK5/6 is expressed in 62.3% (43 of 69) of basal-like TNBCs, and EGFR is expressed in 91.3% (63 of the 69), making these 2 markers helpful when attempting to make a diagnosis of metastatic basal-like TNBC in the appropriate clinical setting. 34 Historically, CK5/6 is the most commonly used basal cytokeratin in determining the basal-like phenotype of TNBC. However, a study 4 reported CK5 positivity in 32 of 33 (97%) of basal-like TNBC tumors and suggested that CK5 is more sensitive than CK5/6 in identifying basal-like TN tumors.…”
Section: Potential Diagnostic Utility Of Basal Cytokeratins and Egfr mentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK and PI3K-AKT signaling pathways were over-activated, suggesting that TNBC cell growth depends on the EGFR signaling pathway (20). High intratumoral EGFR and CK5/6 expression levels may have a role in the development of nodal or distant metastases in TNBC and may be predictive of metastatic disease (21). An EGFR inhibitor has been reported to induce a change from the mesenchymal to the epithelial phenotype in TNBC cells; the EGFR tyrosine kinase inhibitor erlotinib inhibited tumor growth and metastasis in a SUM149 xenograft mouse model (22).…”
Section: Discussionmentioning
confidence: 99%
“…TNBC patients with a basal-like classification have shorter disease-free or overall survival [202,203] and tumors from TNBC patients with metastatic disease exhibit higher levels of K5 and EFGR [204]. A potential influence of HIF-1α on the ability of the K5 and EGFR biomarkers to predict disease-free survival in basal-like TNBC is intriguing in light of our observations that, in cultured cells, EGF stabilizes HIF-1α expression at normoxia and further potentiates hypoxia-inducible expression of HIF-1α.…”
Section: Discussionmentioning
confidence: 99%